Improved Extraction and Quality Characterization of Water‐Soluble Polysaccharide from Gamma‐Irradiated Lentinus edodes. Issue 2 (2nd February 2017) - Akram, Kashif; Shahbaz, Hafiz Muhammad; Kim, Gui‐Ran; Farooq, Umar; Kwon, Joong‐Ho
Abstract: Gamma irradiation was applied to the improved extraction of water‐soluble polysaccharides (WSPs) from dried Lentinus edodes . Irradiation provided a dose‐dependent increase in extraction yield (0 kGy, 2.01%; 7.5 kGy, 4.03%; 15 kGy, 7.17%) and purity (0 kGy, 78.8%; 7.5 kGy, 83.1%; 15 kGy, 85.6%) of the WSPs from hot‐water extraction. The effect of irradiation was evident in the degraded microstructures and reduced molecular weights of the WSPs. However, nuclear magnetic resonance, Fourier‐transform infrared, and X‐ray diffraction spectroscopic analyses provided comparable structures of WSPs from nonirradiated and irradiated samples. UV–visible spectra showed a dose‐dependent decline in intensity, but an improvement in thermal properties of the WSPs from the irradiated mushroom samples was observed.